Burner Design Using Used Oil Fuel Based on Water Vapor Pressure - Afrinaldi, Afrinaldi; Azriadi, Emon; Rusnedy, Hidayati (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This research aims to design and build an environmentally friendly burner that integrates used oil as a fuel based on water vapor pressure and to test the waste combustion efficiency using the designed device. The design stage of the device uses the assistance of AutoCAD. This is followed by direct experimental testing to collect data on the performance and efficiency of waste combustion in the burner. Based on the results of the two burners that have been tested above, it can be concluded that the amount of shrinkage of 8 kg of waste burned in a used oil burner with water vapor pressure is more shrinkage than the used oil burner without water vapor with a difference of 1.1 kg. This can be proven in the best experimental results in the first experiment, namely to burn 8 kg of waste in 25 minutes experiencing a shrinkage of 7.1 kg, so that the efficiency of waste combustion reaches 88.75% in a used oil burner with water vapor pressure. While the used oil burner without water vapor obtained the best results for burning 8 kg of waste in 25 minutes experiencing a shrinkage of 6 kg, so that the efficiency is 75% lower than combustion using a used oil fuel burner using water vapor pressure.